Review paperBone tissue metabolism in psoriatic arthritis patients - Krajewska-Włodarczyk, Magdalena; Samborski, Włodzimierz (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
The chronic inflammatory joint process creates a significant threat to appropriate bone metabolism. In psoriatic arthritis, the loss of bone mass is of a complex nature. The inflammatory cytokines such as interleukin-1, interleukin-6 and tumour necrosis factor α are the major factors causing bone tissue degradation. The circulating precursor cells of osteoclasts also seem to play an important role. The studies on bone tissue metabolism conducted so far in patients from that group, however, are not unequivocal. Regardless of the causes of local and generalised bone destruction, recognition of osteoporosis in psoriatic arthritis is insufficient. Modern arthritis treatment methods developed during the recent decades have a significant influence on bone mass loss inhibiting.